(3GdMQH GdHGQOI Ydi GdcjfhfI GdYQHjI (B/s - (3GdZhK, eNJGQs ((3Mhdj, GdchjJ (B:s (3UhajG,s, 2022)
(3OQS gPG GdcJGH eG CdUb HGdYQHjI ef Jge cGdUYhHI hGdTjNhNI hYOe GdUdGMjI ddYde hCHGf Cf eG fSH EdjgG ef Pdc cGf HYVg aj eYQV GdJHZjV hJShjZ GdOYhI Edi GdJHOd HgG hHjf Cf djS aj GddZI GdEfSGfjI dZI UYHI HEWdGb hCNQi SgdI HEWdGb hCf aj cd dZI eG jUYH heG jSgd hCf UYhHI GddZI Ef aQVJ UMJgG dG JShZ GdJHOd HgG hEfeG jLH YOgG bOQG djS ddTYhH EdG GdJcja eYg(B.s
(3GdeMJhjGJ (B: (3GdLRA (B1. (3GddZI ghjI (B- (3GdLRA (B2. (3GddZI hGdEHOGY hGdJYdje (B- (3GdLRA (B3. (3GdJLfj Ydi GdghjI (B- (3GdLRA (B4. (3cjO GdghjI (B- (3GdLRA (B5. (3GdghjI HYO GdMGOj YTQ ef SHJeHQ(B- (3GdLRA (B6. (3eSN GdghjI (B- (3GdLRA(B7.(1) (3GdUQGY GddZhj bj GdeZQH GdYQHj (B- (3GdLRA(B7.(2) (3GdUQGY GddZhj aj GdeZQH GdYQHj(B.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3GdTNUjI GdYQHjIs; (3GddZI GdYQHjIs -- (3SeGJ GLJeGYjIs -- (3JGQjNs -- (3LhGfH SjGSjIs